PRINCIPLES OF PREVENTING FINANCIAL OFFENSES - Гетманець, Ольга; Добровінський, Артем (SWorldJournal, 2025)
The article examines the principles of preventing financial violations as important components of ensuring national security in the conditions of war in Ukraine. The definition of a financial offense is analyzed and its features are outlined as grounds fo